2022
DOI: 10.3390/genes13030405
|View full text |Cite
|
Sign up to set email alerts
|

Sorbitol Reduces Sensitivity to Alternaria by Promoting Ceramide Kinases (CERK) Expression through Transcription Factor Pswrky25 in Populus (Populus simonii Carr.)

Abstract: Sugar, acting as a signal, can regulate the production of some chemical substance during plant defense responses. However, the molecular basis and regulatory mechanisms of sugar in poplar and other forest trees are still unclear. Sorbitol is a sugar-signaling molecule associated with plant defense. In this study, the pathogen-infested status of poplar was alleviated after exogenous feeding of 50 mM sorbitol. We sequenced and analyzed the transcriptome of poplar leaves before and after inoculation. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The quality of RNA samples were determined by the NanoDrop 8000 (Thermo Fisher Scientific, Waltham, Massachusetts, USA) ( Desjardins and Conklin, 2010 ; Lei et al., 2019 ). Then, using 1 µg RNA as the template, the RNA was reverse transcribed into cDNA using the rapid quantitative RT Supermix Kit (M-MLV Reverse Transcriptase, Mi Si Century Biotechnology company, Shanghai, China) ( Qi et al., 2022 ). The cDNA was stored at - 20 °C for subsequent RT-qPCR experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of RNA samples were determined by the NanoDrop 8000 (Thermo Fisher Scientific, Waltham, Massachusetts, USA) ( Desjardins and Conklin, 2010 ; Lei et al., 2019 ). Then, using 1 µg RNA as the template, the RNA was reverse transcribed into cDNA using the rapid quantitative RT Supermix Kit (M-MLV Reverse Transcriptase, Mi Si Century Biotechnology company, Shanghai, China) ( Qi et al., 2022 ). The cDNA was stored at - 20 °C for subsequent RT-qPCR experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies have shown that PsnWRKY70 enhances poplar resistance to Rhizoctonia allochthonii by activating genes related to pathogen-related molecular patterns (PTI) and effector-induced immunity (ETI) [40]. Exogenous application of sorbitol can further induce PsWRKY25 and PsCERK1 to improve the resistance of P. simonii to diseases [41]. These findings demonstrate the complex disease resistance mechanism of P. In addition to the above, Yuting Wang [42] also characterized 9 PtSROs in Populus plants that can respond to different kinds of abiotic stress.…”
Section: Research Progress Of P Simonii Genomicsmentioning
confidence: 99%
“…It was found that sorbitol exposure increased poplar resistance to A. alternata, and PsWRKY25 was one of the most important effectors: it activated the expression of PsCERK1 (ceramide kinase 1) gene, MAPK cascade genes and secondary metabolites, including phenylpropanoids, biosynthetic genes, etc. Poplar overexpressing PsWRKY25 also had increased resistance to this pathogen [198].…”
Section: Transcription Factors Regulating the Immune Responsementioning
confidence: 99%